دور المدرسة الابتدائية في التوعية المرورية من وجهة نظر أساتذة التعليم الابتدائي -دراسة ميدانية ببعض مدارس بلدية ونوغة ولاية المسيلة- - حبوش امال; ياحي اسيا; اشراف: قرساس حسين (جامعة محمد بوضياف -المسيلة, 2025)
هدفت الدراسة الحالية إلى تقصي دور المدرسة الابتدائية في التوعية المرورية من وجهة نظر أساتذة اللغة العربية ببعض المدارس الابتدائية ببلدية ونوغة، وذلك من خلال التعرف على دور كل من الإدارة المدرسية، البرامج الدراسية، والأساتذة في التوعية المرورية، وللإجابة عن أسئلة الدراسة واختبار فروضها استخدمنا المنهج الوصفي، وتكونت عينة الدراسة من خمسين (50) أستاذا وأستاذة يعملون بخمس مدارس تابعة للمقاطعة التعليمية بونوغة تم اختيارها بطريقة عشوائية. ولجمع المعلومات تم استخدام الاستبيان بعد التحقق من خصائصه السيكومترية من صدق وثبات، وتم الاعتماد على الأساليب الإحصائية التالية: النسبة المئوية، مقياس كاي مربعk2. وتوصلت الدراسة إلى النتائج التالية: - للمدرسة الابتدائية دور إيجابي في التوعية المرورية من وجهة نظر الأساتذة. - للإدارة المدرسية دور إيجابي في التوعية المرورية من وجهة نظر الأساتذة. - للبرامج الدراسية دور إيجابي في التوعية المرورية من وجهة نظر الأساتذة. - للأساتذة دور إيجابي في التوعية المرورية من وجهة نظر الأساتذة. الكلمات المفتاحية: المدرسة الابتدائية - التوعية المرورية - أساتذة التعليم الابتدائي. Abstract: The current study aimed to investigate the role of the primary school in traffic awareness from the point of view of Arabic language teachers in primary schools in the municipality of wanouga, by identifying the role of each of the school administration, study programs, and professors in traffic awareness, and to answer the questions of the study and test its hypotheses we used the descriptive approach, and the study sample consisted of (50) professors in five schools affiliated with the educational district Bonouga was chosen intentionally. To collect information, the questionnaire was used after verifying its psychometric properties of validity and stability, and the following statistical methods were relied upon: percentage, square chi-scale K2. The study found the following results: -The primary school has a positive role in traffic awareness from the teachers' point of view. --The school administration has a positive role in traffic awareness from the point of view of teachers. - Study programs have a positive role in traffic awareness from the point of view of professors. -Professors have a positive role in traffic awareness from the point of view of professors. Keywords: Primary Schoo - Traffic Awareness –– Primary School Teachers.